PARENTS' PERCEPTIONS OF ONLINE LEARNING ASSISTANCE DURING THE COVID-19 PANDEMIC AT AL ITTIHAD Kindergarten - suharni_86 (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2021)
This study aims to present information about parents' perceptions of online learning assistance due to the COVID-19 pandemic that has spread throughout the world, including Indonesia. This is very detrimental to all parties, including the world of education. Due to the COVID-19 pandemic, early childhood education must continue to be implemented so that children's rights in education are still accepted by early childhood. Children still have to follow the learning process so that they continue to receive education at home with parental assistance. But of course, online learning is a challenge for parents who do not work and those who work, so that it creates perceptions in every parent of students.